Адміністративні правовідносини за участю органів Державного бюро розслідувань - Комзюк, А. Т.; Komziuk, A. T.; Липій, Є. А.; Lypii, Ye. A.; Anatolii Komziuk (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 1 (104), ч. 1. - С. 109-123, 2024)
Визначено сутність, особливості та види адміністративно-правових відносин, учасниками яких є органи Державного бюро розслідувань. Надано загальну характеристику адміністративно-правових відносин, які виокремлюються з їх загальної сукупності завдяки особливостям сфери виникнення, колу учасників (суб’єктів) і змісту. Розглянуто особливості статусу Державного бюро розслідувань як правоохоронного органу. Охарактеризовано види адміністративних правовідносин, учасниками яких можуть бути органи Державного бюро розслідувань. Наголошено, що переважно йдеться про внутрішньоорганізаційні відносини в цих органах, хоча вони можуть брати участь і в деяких відносинах публічного управління. Сформульовано пропозиції та рекомендації щодо вдосконалення правових засад адміністративних правовідносин за участю органів Державного бюро розслідувань.

The essence, characteristics, and types of administrative legal relations involving the State Bureau of Investigations have been identified. Additionally, suggestions and recommendations for improving the legal foundations of these relations have been formulated. A comprehensive description of administrative legal relations that stand out from the broader array due to specific aspects of their emergence, participants (subjects), and content has been provided. This encompasses the nature and various types of subjective rights and obligations that manifest within these relations. It is emphasized that these relations occupy a distinct sphere of formation and evolution, specifically within the realm of public administration. Concerning the interplay between subjects of public administration and subjects of administrative legal relations, it is underscored that public administration is exclusively outwardly focused, with internal organizational relations within certain bodies not falling under its purview. On the other hand, administrative legal relations encompass internal organizational dynamics (intra-system, intra-administrative) within any state entity. These relations are recognized as a distinct component within the subject matter of administrative law. It is emphasized that the leading place among the subjects of administrative legal relations is occupied by public authorities, which, according to the law, include the State Bureau of Investigation. At the same time, these bodies have a rather different administrative and legal status, since their participation in public administration varies significantly. Attention is drawn to the problem of the existence of state bodies which are not attributed to any of the branches of power, and their number is growing, currently there are about fifteen of them, including the State Bureau of Investigation. The article concludes that the bodies outside the branches of power defined by the Constitution of Ukraine are not structurally part of these branches, although this does not mean that they do not participate in the exercise of public authority. The types of administrative legal relations which may arise in the State Bureau of Investigation have been identified and characterised. It is emphasised that these are mainly intra-organisational relations within these bodies, since their purpose is to counteract crimes committed by law enforcement officers, judges and senior civil servants, i.e. their external activities are generally not managerial and are not regulated by administrative and legal provisions.

Определены сущность, особенности и виды административно-правовых отношений, участниками которых являются органы Государственного бюро расследований. Дана общая характеристика административно-правовых отношений, которые выделяются из их общей совокупности благодаря особенностям сферы возникновения, кругу участников (субъектов) и содержанию. Рассмотрены особенности статуса Государственного бюро расследований как правоохранительного органа. Охарактеризованы виды административного правоотношения, участниками которых могут быть органы Государственного бюро расследований. Отмечено, что в основном речь идет о внутриорганизационных отношениях в этих органах, хотя они могут участвовать и в некоторых отношениях публичного управления. Сформулированы предложения и рекомендации по усовершенствованию правовых основ административных правоотношений с участием органов Государственного бюро расследований.
Administrative legal relations with the participation of the State Bureau of Investigation
Keywords: правовідносини; адміністративні правовідносини; виконавча влада; публічне управління; суб’єкти; Державне бюро розслідувань; внутрішньоорганізаційні відносини; legal relations; administrative legal relations; executive power; public administration; subjects; State Bureau of Investigation; internal organisational relations; правоотношения; административное правоотношение; исполнительная власть; публичное управление; субъекты; Государственное бюро расследований; внутриорганизационные отношения